Maize defense elicitor, 12-oxo-phytodienoic acid, prolongs aphid salivation. Issue 1 (1st January 2020) - Grover, Sajjan; Varsani, Suresh; Kolomiets, Michael V.; Louis, Joe
ABSTRACT: 12-﻿Oxo-phytodienoic acid (OPDA), an intermediate in the jasmonic acid (JA) biosynthesis pathway, regulates diverse signaling functions in plants, including enhanced resistance to insect pests. We previously demonstrated that OPDA promoted enhanced callose accumulation and heightened resistance to corn leaf aphid (CLA; Rhopalosiphum maidis ), a phloem sap-sucking insect pest of maize ( Zea mays ). In this study, we used the electrical penetration graph (EPG) technique to monitor and quantify the different CLA feeding patterns on the maize JA-deficient 12-oxo-phytodienoic acid reductase ( opr7opr8 ) plants. CLA feeding behavior was unaffected on B73, opr7opr8 control plants (- OPDA), and opr7opr8 plants that were pretreated with OPDA (+ OPDA). However, exogenous application of OPDA on opr7opr8 plants prolonged aphid salivation, a hallmark of aphids' ability to suppress the plant defense responses. Collectively, our results indicate that CLA utilizes its salivary secretions to suppress or unplug the OPDA-mediated sieve element occlusions in maize.